A B4C-WB2 composite material and preparation method thereof

By using micron-level WB2 and B4C with nanosheet-like structure, combined with high-temperature and high-pressure sintering process, WB2 is uniformly distributed in B4C, and the problem of insufficient hardness and fracture toughness of boron carbide composite materials in the prior art is solved, and high B4C-WB2 composite material with hardness and high fracture toughness, and simplifies the preparation process.

CN118580079BActive Publication Date: 2025-02-07JILIN INST OF CHEM TECH
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202410709602.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-03
Publication Date
2025-02-07
Estimated Expiration
2044-06-03

AI Technical Summary

Technical Problem

The prior art is difficult to simultaneously improve the hardness and fracture toughness of boron carbide composite materials, and there are problems of agglomeration and excessive preparation period during the preparation process.

Method used

Micron-level WB2 and B4C with nanosheet-like structure are used as raw materials, and WB2 is evenly distributed in B4C through high-temperature and high-pressure sintering process to form a block B4C-WB2 composite material.

Benefits of technology

A composite material with high hardness (convergence hardness is 31GPa) and high fracture toughness (fracture toughness is 4.94MPa·m0.5) was achieved, which simplified the preparation process and shortened the preparation cycle.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118580079B_ABST
    Figure CN118580079B_ABST
Patent Text Reader

Abstract

The invention discloses a B4C-WB2 composite material and a preparation method thereof, which belongs to the technical field of hard composite material preparation, and is composed of micron-level WB2 and B4C with a nano-sheet structure; the WB2 is uniformly distributed in the B4C. The invention first synthesizes micron-level WB2 with high hardness and high fracture toughness and B4C with a nano-sheet structure, and then, through high-temperature and high-pressure sintering, the micron-level WB2 is uniformly distributed between the B4C layers with a nano-sheet structure to form a B4C-WB2 composite material, wherein the WB2 can be uniformly distributed in the B4C without forming agglomerations, and exhibits high hardness and high fracture toughness.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of preparation of hard composite materials, and in particular relates to a B4C-WB2 composite material and a preparation method thereof. Background Art

[0002] Boron carbide (B4C) is widely used in cutting tools, wear-resistant parts, ball mills, etc. due to its high melting point, high hardness, low density, good chemical stability, good wear resistance and high neutron absorption cross section. In addition, it can also be used as neutron absorption and shielding materials in the nuclear industry. However, there are still two important problems that limit the further application of boron carbide in industry. First, the chemical bond of boron carbide is very strong, and it is difficult to synthesize a high-density boron carbide composite material, which in turn affects its hardness (the hardness is below 30GPa); second, the fracture toughness is very poor.

[0003] People have used many methods to try to improve the hardness and fracture toughness of samples at the same time. The most commonly used method is to add sintering aids for hot pressing sintering. Pressure and temperature can improve the density of the sample. The additives can fill the gaps of boron carbide and form grain boundaries to improve the hardness and toughness of the sample. Initially, people tried to use metal as an additive. However, when the temperature was too low, the metal did not react with boron carbide. Due to the presence of metal, the hardness was low; when the temperature increased, the metal reacted with boron carbide to generate metal boride and carbon. At this time, the hardness was determined by the amount of metal boride generated and the hardness of the generated metal boride. The greater the hardness of the metal boride, the greater the hardness of the prepared composite material. In addition, since the generated metal boride has good fluidity, it will form metal agglomerates, which greatly reduces the hardness of the composite material. Although the test hardness of some composite materials is very high, the pin indentation of the test hardness is all pressed on B4C, and the measured hardness value is actually the hardness of B4C.

[0004] Patent CN106478112A discloses a high-hardness and high-toughness B4C-W2B5 composite ceramic and its preparation method. The preparation method of the composite ceramic includes two methods, one using B powder and WC powder as raw materials, and the other using B powder, C powder and WC powder as raw materials, and is prepared by an in-situ synthesis method. Specifically, the raw material powder is first dry-milled using a ball mill to obtain a uniformly mixed abrasive; then pre-pressed into shape; and finally placed in a sintering furnace for sintering. The B4C-W2B5 composite ceramic prepared by the present invention has excellent comprehensive properties: the densification temperature is only 1700°C, the hardness is 28.8-37.9GPa), and the fracture toughness is 7.8-10.9MPa·mm 1 / 2 From the measured values ​​alone, it can be seen that the hardness and fracture toughness of the prepared composite ceramics are good, but from the scanning electron microscope micrographs of the prepared composite ceramic materials ( Figure 1) can be clearly seen that a large number of agglomeration problems have occurred in the composite material, and the agglomerated material is surrounded by free carbon and metal boride. In the hardness test, the sample needs to be polished, and the B4C material with high hardness in the composite material can form a test area with a smooth surface. The hardness indentation is just at the micron level. Therefore, the hardness value measured is the B4C material agglomerated in the synthetic sample, and it is not a uniform hardness value. In industrial applications, it is required to be uniformly stressed everywhere, and it is easy to break at free carbon and metal boride. Therefore, the numerical value measured cannot reflect the overall hardness and fracture toughness of the composite material. In addition, the preparation cycle and sintering time required for the preparation of this method are too long, which is not suitable for industrial promotion.

[0005] Due to the above problems in the prior art, the obtained composite materials have problems of insufficient strength and short service life in practical applications. Therefore, the art urgently needs a boron carbide composite material in which the composite components can be evenly distributed, so as to truly improve the hardness and fracture performance of the composite material. Summary of the invention

[0006] The purpose of the present invention is to provide a B4C-WB2 composite material and a preparation method thereof to solve the problems existing in the above-mentioned prior art. The present invention uses B4C with a nano-sheet structure and WB2 at the micron level as raw materials to synthesize a B4C-WB2 composite material with high hardness (convergent hardness of 31GPa) and high fracture toughness (fracture toughness of 4.94MPa·m 0.5 ) bulk B4C-WB2 composite material, which can be used as a multifunctional hard material in industrial production.

[0007] One of the technical solutions provided by the present invention:

[0008] A B4C-WB2 composite material consists of micron-scale WB2 and B4C with a nano-sheet structure; the WB2 is uniformly distributed in the B4C.

[0009] In the B4C-WB2 composite material, WB2 is uniformly distributed in B4C, the WB2 material with better toughness will not form micron-level agglomerations in the composite material, and the grain boundaries are in a growth relationship.

[0010] The second technical solution provided by the present invention is:

[0011] A method for preparing the above-mentioned B4C-WB2 composite material comprises the following steps: firstly, micron-sized WB2 and B4C with a nano-sheet structure are crushed separately, and then the B4C-WB2 composite material is prepared by grinding and mixing, briquetting, assembling, a first synthesis reaction and cooling and decompression.

[0012] The specific preparation method is as follows: using micron-level WB2 and B4C with a nano-sheet structure as raw materials, crushing the raw materials, grinding and mixing, briquetting, assembling, high-temperature and high-pressure synthesis, cooling and decompression, and obtaining a block B4C-WB2 composite material; the raw material crushing refers to wrapping the micron-level WB2 and the B4C with a nano-sheet structure with molybdenum sheets respectively and smashing them with a hammer, the grinding and mixing refers to grinding and mixing the crushed raw materials in an agate mortar, the briquetting refers to using a hydraulic press to press the ground and mixed powder mixture into a cylindrical raw material with a diameter of 4mm and a thickness of 3mm according to the size of the synthesis cavity, and putting the cylindrical raw material into a synthesis tool as a reaction raw material, the assembly refers to loading the cylindrical raw material into a heating container and putting it into the synthesis cavity, the high-temperature and high-pressure synthesis is to keep the temperature and pressure for 15 minutes under the conditions of a pressure of 5.0GPa and a temperature of 2200°C, and the cooling and decompression is to stop the power heating and let the assembly block cool naturally to room temperature, and then reduce the pressure to normal pressure to obtain a block B4C-WB2 composite material.

[0013] The WB2 prepared by the present invention is a material with high hardness and high fracture toughness. It is evenly distributed in B4C with a nano-sheet structure, and no free carbon and metal clusters are generated during the reaction, thereby improving the hardness and fracture toughness of the composite material.

[0014] Preferably, the grain size of the WB2 is 250-350 nm.

[0015] Preferably, the mass ratio of WB2 to B4C is 5:1.

[0016] When the temperature rises, the generated B4C-WB2 composite material gradually becomes denser. The higher the temperature, the denser the sample. At the same time, the higher the pressure, the denser the sample. Therefore, the preparation conditions selected by the present invention for synthesizing the B4C-WB2 composite material are: the pressure of the first synthesis reaction is 5.0 GPa, the temperature is 2200°C, and the temperature and pressure are kept for 15 minutes.

[0017] Preferably, the method for preparing the B4C having a nano-sheet structure comprises: using B4C powder as a raw material, carrying out briquetting, assembly, a second synthesis reaction and cooling and decompression to prepare B4C having a nano-sheet structure.

[0018] More preferably, the temperature of the second synthesis reaction is 2200° C., the pressure is 5.0 GPa, and the time of heat and pressure preservation is 15 minutes.

[0019] The temperature of the second synthesis reaction is an important factor affecting the density of the synthetic material B4C. When the temperature rises, the generated B4C gradually becomes denser. The higher the temperature, the denser the sample.

[0020] Preferably, the preparation method of the WB2 is: tungsten powder and amorphous boron powder are mixed in a molar ratio of 1:2.2, and subjected to briquetting, assembly, a third synthesis reaction, and cooling and decompression to prepare the WB2.

[0021] More preferably, the temperature of the third synthesis reaction is 1600° C., the pressure is 5.0 GPa, and the time of heat and pressure preservation is 15 minutes.

[0022] Beneficial effects of the present invention:

[0023] The present invention firstly synthesizes micron-sized WB2 with high hardness and high fracture toughness and B4C with a nano-sheet structure, and then evenly distributes the micron-sized WB2 between B4C layers with a nano-sheet structure through high-temperature and high-pressure sintering to form a B4C-WB2 composite material. WB2 can be evenly distributed in B4C without agglomeration and exhibits high hardness and high fracture toughness.

[0024] The preparation process of the B4C-WB2 composite material provided by the present invention is simple and will not cause air pollution or waste of resources.

[0025] The B4C-WB2 composite material prepared by the present invention has high hardness and high fracture toughness. The prepared composite material is a block material, which is conducive to testing mechanical properties and electrical properties.

[0026] The preparation method of the B4C-WB2 composite material provided by the present invention greatly shortens the preparation cycle and sintering time of the traditional method. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0028] Figure 1 This is a scanning electron microscope micrograph of the B4C-W2B5 composite ceramic prepared by patent CN106478112A;

[0029] Figure 2 It is a schematic diagram of the assembly of the present invention;

[0030] Figure 3 is the X-ray diffraction pattern of the B4C sample prepared in Example 1, wherein (a), (b) and (c) are the X-ray diffraction patterns of the B4C samples synthesized at 1800° C., 2000° C. and 2200° C., respectively;

[0031] Figure 4are scanning electron microscope images of the B4C sample prepared in Example 1, wherein (a), (b) and (c) are scanning electron microscope images of the B4C samples synthesized at 1800° C., 2000° C. and 2200° C., respectively, and (d) is a scanning electron microscope image of the sample synthesized at 2200° C. at a high magnification;

[0032] Figure 5 is the X-ray diffraction pattern of the WB2 sample prepared in Example 2;

[0033] Figure 6 are scanning electron microscope images of the WB2 sample prepared in Example 2, wherein (a), (b), (c) and (d) are scanning electron microscope images of the WB2 sample synthesized at 1600° C., 1700° C., 1800° C. and 1900° C., respectively;

[0034] Figure 7 The hardness test data of the sample synthesized in Example 2 at a temperature of 1600°C;

[0035] Figure 8 is the X-ray diffraction pattern of the B4C-WB2 composite material prepared in Example 3;

[0036] Fig. 9 The scanning electron microscope images of the B4C-WB2 composite material prepared in Example 3, wherein (a) and (b) are scanning electron microscope images with magnifications of 10,000 times and 50,000 times, respectively;

[0037] Fig.10 Element distribution of the B4C-WB2 composite material obtained in Example 3, wherein (a) is a scanning electron microscope image of the B4C-WB2 composite material at a magnification of 10,000 times, wherein (b) is a boron element distribution map, (c) is a carbon element distribution map, and (d) is a tungsten element distribution map;

[0038] Fig.11 This is an indentation picture of the hardness test of the B4C-WB2 composite material prepared in Example 3. DETAILED DESCRIPTION

[0039] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0040] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0041] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0042] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present application description and examples are exemplary only.

[0043] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0044] The room temperature in the present invention refers to 25±2°C.

[0045] The embodiment of the present invention provides a method for preparing a B4C-WB2 composite material, wherein B4C with a nano-sheet structure and micron-level WB2 are used as raw materials, and a block B4C-WB2 composite material is prepared through a process of raw material crushing, grinding and mixing, briquetting, assembling, high-temperature and high-pressure synthesis, and cooling and pressure relief; wherein the raw material briquetting is to crush, grind and mix the synthesized B4C with a nano-sheet structure and micron-level WB2, and then use a cold press to press it into a cylindrical raw material with a diameter of 4 mm and a thickness of 3 mm, and put it into a synthesis tool as a reaction raw material, wherein the assembly is to load the cylindrical raw material into a heating container and put it into a synthesis cavity, wherein the high-temperature and high-pressure synthesis is to put the sample into a six-sided hydraulic press, and keep it warm and pressurized at a pressure of 5.0 GPa and a temperature of 2200°C for 15 minutes, wherein the cooling and pressure relief is to stop the power heating and let the assembly block cool naturally to room temperature, and then reduce the pressure to normal pressure, Figure 2 It is a schematic diagram of the assembly of the present invention.

[0046] The embodiment of the present invention is completed on a domestic SPD-6×600 six-sided top press.

[0047] In order to ensure the uniformity of the temperature of the synthesis cavity during the synthesis of the sample, the heating method adopted by the present invention is the heating of the graphite tube by the power supply. In order to ensure that the sample does not react with the graphite tube that generates heat, the cavity of the synthesis sample is protected by hexagonal boron nitride.

[0048] Example 1

[0049] B4C micropowder with a purity of 99.9% was used as raw material. A hydraulic press was used to press the B4C micropowder into a cylindrical B4C sample with a diameter of 4 mm and a thickness of 3 mm according to the size of the synthesis cavity. The cylindrical B4C sample was loaded into the synthesis cavity. A graphite heat pipe was used as a heating material in the synthesis cavity, pyrophyllite was used as an insulation material, and hexagonal boron nitride was used to protect the sample from contamination. The synthesis pressure was set to 5.0 GPa, and the synthesis temperatures were set to 1800°C, 2000°C and 2200°C, respectively. The pressure and temperature were maintained for 15 minutes, and the heating was stopped. The sample was naturally cooled to room temperature and then the pressure was released to prepare B4C samples with different synthesis temperatures.

[0050] Figure 3 The X-ray diffraction pattern of the B4C sample prepared in this example is: Figure 3 (a), (b) and (c) are X-ray diffraction patterns of B4C samples synthesized at 1800℃, 2000℃ and 2200℃, respectively. Figure 3 It can be seen that the synthesized B4C samples are all pure phase samples.

[0051] Figure 4 is a scanning electron microscope image of the B4C sample prepared in this embodiment, Figure 4 (a), (b) and (c) are SEM images of B4C samples synthesized at 1800℃, 2000℃ and 2200℃ respectively. Figure 4 It can be seen that the B4C sample prepared in this example is very dense; Figure 4 (d) is a high magnification image of the sample synthesized at 2200°C. As can be seen from (d), the B4C sample synthesized at 2200°C has a nanosheet structure.

[0052] Example 2

[0053] Tungsten powder with a purity of 99.99% and amorphous boron powder with a purity of 99.99% were used as raw materials, and the tungsten powder and amorphous boron powder were mixed at a molar ratio of 1:2.2. The mixed powder was pressed into a cylindrical WB2 sample with a diameter of 4 mm and a thickness of 3 mm by a hydraulic press according to the size of the synthesis cavity. The cylindrical WB2 sample was assembled in the same manner as in Example 1, the synthesis pressure was set to 5.0 GPa, and the synthesis temperatures were set to 1600°C, 1700°C, 1800°C and 1900°C, respectively. The pressure and temperature were maintained for 15 minutes, and the heating was stopped. The sample was naturally cooled to room temperature and then the pressure was released to prepare WB2 samples at different synthesis temperatures.

[0054] Figure 5 The X-ray diffraction pattern of the WB2 sample prepared in this example is as follows: Figure 5 It can be seen that the WB2 samples synthesized in this embodiment are all pure phase samples.

[0055] Figure 6 is a scanning electron microscope image of the WB2 sample prepared in this embodiment, Figure 6 (a), (b), (c) and (d) are SEM images of WB2 samples synthesized at 1600℃, 1700℃, 1800℃ and 1900℃, respectively. Figure 6 It can be seen that the higher the synthesis temperature, the larger the grain size of the sample. When the grain size is too large, it is not conducive to doping it into the nanosheet structure B4C. Therefore, the present invention selects the WB2 sample prepared at 1600°C as the raw material for further synthesis of the B4C-WB2 composite material. The particle size range is measured to be about 300nm.

[0056] The Vickers hardness of the sample was measured using a microhardness tester (HV-1000ZDT). The sample was double-sided polished before the hardness test. The test load was 0.25N-4.9N. The hardness value was calculated by taking the average value of 8 measurements under each load. The Vickers hardness value was calculated by the following formula:

[0057] Hv=1854.4P / d 2

[0058] Where d is the average length of the indentation diagonal in micrometers; P is the applied load in N; Hv represents the Vickers hardness in GPa.

[0059] Figure 7 The hardness test data of the sample synthesized in this embodiment at 1600°C is 25.5 GPa. Figure 7 It can be seen that the sample still does not break under the condition of a pressure load of 4.9N, and there is no crack on the hardness pressing edge, which shows that the fracture toughness of the sample is very good, the sample has good density and has the ductility of metal.

[0060] Example 3

[0061] The B4C with nano-sheet structure synthesized at 2200°C in Example 1 and the micron-level WB2 synthesized at 1600°C in Example 2 were used as raw materials, with a raw material ratio of B4C:WB2=5:1. The B4C and B4C were wrapped with molybdenum sheets respectively, smashed with a hammer, and the two smashed raw materials were crushed and fully mixed using an agate mortar. The ground powder sample was pressed into a cylindrical B4C-WB2 sample with a diameter of 4 mm and a thickness of 3 mm using a hydraulic press according to the size of the synthesis cavity. The cylindrical B4C-WB2 sample was assembled in the same manner as in Example 1, the synthesis pressure was set to 5.0 GPa, the synthesis temperature was set to 2200°C, the pressure was maintained for 15 minutes, the heating was stopped, and the sample was naturally cooled to room temperature and then the pressure was released to prepare a B4C-WB2 composite material.

[0062] Figure 8 The X-ray diffraction pattern of the B4C-WB2 composite material prepared in this embodiment is as follows: Figure 8 It can be seen that the synthesized sample only contains a mixed phase of B4C and WB2, and there is no free carbon or metal phase. Fig. 9 is a scanning electron microscope image of the B4C-WB2 composite material prepared in this embodiment, Fig. 9 (a) and (b) are scanning electron microscope images with magnifications of 10,000 and 50,000 times, respectively. Fig. 9 It can be seen that under different magnifications, the B4C-WB2 composite material prepared in this example is in a homogeneous state and also exhibits a lamellar structure in the macroscopic view.

[0063] Fig.10 Element distribution of the B4C-WB2 composite material obtained in this embodiment, wherein (a) is a scanning electron microscope image of the B4C-WB2 composite material at a magnification of 10000 times, (b) is a boron element distribution map, (c) is a carbon element distribution map, and (d) is a tungsten element distribution map. Fig.10 It can be seen that the tungsten element is evenly distributed in the sample, indicating that WB2 is evenly distributed in the B4C-WB2 composite material without agglomeration.

[0064] Performance test experiment

[0065] The hardness and fracture toughness of the B4C-WB2 composite material prepared in Example 3 were measured.

[0066] The samples were double-sided polished to ensure a clean and flat surface. The D5000 produced by Siemens in Germany was used for X-ray diffraction (XRD) testing, and the samples were subjected to phase analysis to determine the type of samples and whether the samples were pure phases. The surface morphology and crystal structure of the samples were characterized using a JEOL JSM-6700F field emission scanning electron microscope produced in Japan. The Vickers hardness of the samples was measured using an instrument model HV-1000ZDT microhardness tester. During the test, the load was selected to be 0.49-9.8N, and multiple sets of data were measured. Each set needed to stay for 15 seconds to obtain the hardness value of the sample, and after obtaining the indentation, the fracture toughness of the sample was calculated using the formula, which is:

[0067] K 1c =0.203Hva 1 / 2 (c / a) -3 / 2

[0068] Where Hv is the Vickers hardness, a is the indentation radius, and c is the longitudinal / transverse fracture length.

[0069] The hardness test showed that the convergent hardness of the B4C-WB2 composite material prepared in Example 3 was 31 GPa, and the fracture toughness was 4.94 MPa·m 0.5 , hardness test indentation pictures such as Fig.11 As shown, Fig.11 The indentation image is obtained under the condition of pressure load of 9.8N. Fig.11 It can be seen that the sample still does not break under such a high pressure load, and the crack lengths in the two directions are different, which may be caused by the anisotropy of the nanosheet structure. The pure phase B4C synthesized by the present invention has a much higher hardness than the B4C synthesized by the conventional method. The hardness of the B4C synthesized by the conventional method is about 36GPa. The B4C synthesized by the present invention is B4C with a nanosheet structure. When the nanostructure is tested for hardness, the nano grain boundary can resist the slip of the grain boundary and the fracture of the grain. Therefore, the hardness value of the B4C-WB2 composite material synthesized by the present invention under high pressure load has a high hardness of 31GPa, and the sample is uniform, which has very high industrial application value.

[0070] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.

Claims

1. A B4C-WB2 composite material, characterized in that: It is composed of micron-sized WB2 and B4C with a nano-sheet structure; the WB2 is evenly distributed in the B4C; The preparation method of the B4C-WB2 composite material comprises the following steps: firstly, micron-sized WB2 and B4C with a nano-sheet structure are crushed respectively, and then the B4C-WB2 composite material is prepared by grinding and mixing, briquetting, assembling, a first synthesis reaction and cooling and decompression; The grain size of WB2 is 300nm; The mass ratio of B4C to WB2 is 5:1; The preparation method of WB2 is: tungsten powder and amorphous boron powder are mixed in a molar ratio of 1:2.2, and subjected to briquetting, assembly, a third synthesis reaction, and cooling and decompression to prepare WB2; The temperature of the third synthesis reaction is 1600°C, the pressure is 5.0 GPa, and the time of heat preservation and pressure preservation is 15 minutes; The temperature of the first synthesis reaction is 2200° C., the pressure is 5.0 GPa, and the time of heat and pressure preservation is 15 minutes.

2. The B4C-WB2 composite material according to claim 1, characterized in that: The preparation method of the B4C with a nano-sheet structure comprises: using B4C micropowder as a raw material, carrying out briquetting, assembly, a second synthesis reaction and cooling and decompression to prepare the B4C with a nano-sheet structure.

3. The B4C-WB2 composite material according to claim 2, characterized in that: The temperature of the second synthesis reaction is 2200° C., the pressure is 5.0 GPa, and the time of heat and pressure preservation is 15 minutes.

Citation Information

Patent Citations

  • High-hardness high-toughness B4C-W2B5 composite ceramic and preparation method thereof

    CN106478112A